THE EFFECT OF PROJECT-BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN PRODUCTIVE SUBJECTS CLASS XII TKJ AT SMK NEGERI 1 REJOTANGAN - Andhika Bagas Surya; Bian Dwi Pamungkas; Farid Sukmana (STKIP PGRI TULUNGAGUNG, 2024)
This research is motivated by the low learning outcomes of students in class XII of SMKN 1 Rejotangan. The purpose of this study was to determine the effect of the use of PJBL learning model on the learning outcomes of XII grade students of SMK Negeri 1 Rejotangan. The research design used a quantitative approach with a research design of Quasi Experiment Nonequivalent Pretest-Posttest Control Group Design. The experimental class was taught using a project-based learning model and the control class used a conventional learning model, namely using a lecture learning model. The learning outcome test obtained shows that the average value of the experimental group is 72.56 and the average value of the control group is 58.84. Based on the hypothesis test, the sig value equal 0.000 at a significant level of alpha equal 0.05. This means that the sig value is less 0.05, which means that the sig value is outside the H0 acceptance area. So it can be concluded that there is an effect of the application of the PJBL learning model on the learning outcomes of XII grade students of the TKJ Department of SMK Negeri 1 Rejotangan